Pertumbuhan dan Hasil Padi Sawah Organik pada Berbagai Jenis dan Waktu Aplikasi Pupuk Hijau Legum Tahunan - Marti Winarni (Universitas Merdeka Madiun, 2022)
Abstract— Green manure is a source of soil organic matter and nutrients for organic lowland rice, especially nitrogen. The use of various species of perennial legume green manure as a source of nitrogen that the right application time is not widely reported. The research objectives are to examine the effect of the interaction of application time of several species of perennial legume green manure on physiological characteristics, growth and yield of organic lowland rice, and to find the right application time of several species of perennial legume green manure to support growth and organic rice yields. We used a factorial RCBD, consisting of two factors and three groups, and control. The first factor is the species of perennial legume green manure, consisting of four species, namely: Turi, Gliricidia, Lamtoro, and Cow Manure. The second factor is the time of application of perennial legume green manure, consisting of three levels, namely: 4 weeks before planting rice seeds, 2 weeks before planting rice seeds, and at the same time planting rice seeds. The results showed that the growth and yield of organic lowland rice was influenced by the species and timing of perennial legume green manure application. The optimal application time to Turi leaves is 1.06 weeks before planting rice seeds with grain yield 9.29 t/ha, the optimal application time to Gliricidia leaves is 1.85 weeks before planting with grain yield 10.24 t/ha, and the optimal application time Lamtoro leaves is 2.58 weeks before planting with grain yield of 9.78 t/ha.